Effect of liuzijue qigong on patients with stable chronic obstructive pulmonary disease: A systematic review and meta-analysis. Issue 41 (15th October 2021) - Gao, Pincao; Tang, Fang; Liu, Weiguo; He, Kai; Mo, Yu
Abstract: Backgrounds: Chronic obstructive pulmonary disease (COPD) is a common, preventable disease of airflow limitation that accounts for the third leading deaths of any disease process in the worldwide. Health benefits of liuzijue qigong (LQG) on patients with stable COPD has been assessed. This study was designed to perform a systemic review and meta-analysis of the effect of Liuzijue breathing exercise on patients with stable COPD. Methods: Published articles from 1970 to December 2020 were conducted using electronic searches. Two independents reviewers conducted data extraction. The Cochrane risk of bias assessment tool was used to evaluate the quality of the included studies. Results: A total of 16 eligible trials with 1039 patients with stable COPD were identified. Compared with control group, the pool meta-analysis of LQG showed a significant improvement in forced expiratory volume in one second (FEV1) (MD = −0.16, 95% CI [0.09, 0.23], P < .00001), FEV1% (MD = 9.71, 95% CI [8.44, 10.98], P < .00001), the ratio of forced expiratory volume to forced vital capacity in the first second (FEV1/FVC [%]) (MD = 4.81, 95% CI [2.12, 7.51], P = .0005), 6 minutes walking distance (6MWD) (MD = 21.89, 95% CI [14.67, 29.11], P < .00001), health-related quality of life (SMD = −0.84, 95% CI [−1.12, -0.55], P < .00001) and modified medical research council dyspnea scale (mMRC) (MD = −0.73, 95% CI [−0.96, −0.50], P < .00001). The observed effect was more pronounced for short term and medium-term duration interventions of study. It also showed improvements in the secondary outcome measures by LQG. Conclusions: In this systematic review and meta-analysis, LQG can improve lung ventilation function, exercise endurance and health-related quality of life of patients with stable COPD. Ethic and dissemination: This study is a systematic review and it does not involve harming to the rights of participants. Ethical approval will not be require for this study. The research results may be published in a peer-reviewed journals.